Biotechnology innovation adoption: a comparison between university and company perspectives - Farid, Hadi; Silong, Abu Daud; Ismail, Ismi Arif; Hamzah, Azimi; Sarkar, Saroje Kumar (IDOSI Publications, 2012)
Researchers are producers of biotechnology innovations and agricultural biotechnology companies are potential users of them. Providing a linkage between these parties can be beneficial for both. Especially in Malaysia where the level of agriculture biotechnology adoption is low compared to other countries, providing the knowledge to build this linkage seems a necessity. This study tended to find the predictors of level of biotechnology innovations adoption in biotechnology companies from the perspective of both university biotechnology experts and biotechnology companies. The significant influence found for factors of knowledge, cooperation and acceptance indicates the effectiveness of these factors to encourage innovation adoption. Fund and transfer of technology were found to be in effect causes of biotechnology innovation adoption. Comparing the data exhibits that the most powerful predictor to increase the level of adoption is the amount of fund allocated to adopting companies by the government.